2022
DOI: 10.1186/s12913-022-08892-5
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and skills of pre-eclampsia management among healthcare providers working in antenatal clinics in Zanzibar

Abstract: Background Pre-eclampsia and eclampsia are the leading causes of perinatal morbidity and mortality worldwide. Early detection and treatment of preeclampsia is lifesaving; however, evidence suggests that the majority of women in low and middle income-countries are not routinely screened for high blood pressure during antenatal care, that those with severe and mild pre-eclampsia are not monitored for blood pressure and proteinuria as needed, and the magnesium sulphate is not administered as neede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
3
1
0
Order By: Relevance
“…Moreover study also showed those who get on job training as statistically significant,this was similar to study done in Zanzibar showed those get on job training had knowledge. 18 This was similar to a study conducted in Dar-es-Salaam -Tanzania, Bangladesh, and Nigeria, the result showed those who did not get on-job training have less knowledge than those who get training. Possibly the reason for similarities could be geographical location.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Moreover study also showed those who get on job training as statistically significant,this was similar to study done in Zanzibar showed those get on job training had knowledge. 18 This was similar to a study conducted in Dar-es-Salaam -Tanzania, Bangladesh, and Nigeria, the result showed those who did not get on-job training have less knowledge than those who get training. Possibly the reason for similarities could be geographical location.…”
Section: Discussionsupporting
confidence: 86%
“… 16 Again, a similar study done in Bujumbura reviels knowledge gap pertaing to hypertension in pregnancy among health care providers 17 moreover study conducted in Zanzibar reviels inadequate knowledge of service providers. 18 The reason for deference in results could be; geographical location, sample size, method of analysis and type of respondents.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that there is a need to provide refresher trainings about maternal and neonatal complications that may occur before, during, and after childbirth. The findings from this study corroborate those of studies conducted from different low resources countries across the globe [18][19][20][21], that established the need for providing adequate and regular trainings on EmONC for nurses at primary health level to enable them recognize the risk factors of preeclampsia, and be able to confirm it so that prophylactic interventions to manage it are initiated earlier. This finding also supports the results of a similar study conducted in Rwanda that highlighted lack of regular and continuous trainings for nurses and midwives about EmONC as a constraint to managing emergency maternal and neonatal complications [21].…”
Section: Discussionsupporting
confidence: 85%
“…Particularly, our study found that there is a need to provide refresher trainings about the management of pre-eclampsia. The findings from this study corroborate those of studies conducted from different low resources countries across the globe [24][25][26][27], that established the need for providing adequate and regular trainings on EmONC for nurses at primary health level to enable them recognize the risk factors of preeclampsia, and be able to confirm it so that prophylactic interventions to manage it are initiated earlier. This finding also supports the results of a similar study conducted in Rwanda that highlighted lack of regular and continuous trainings for nurses and midwives about EmONC as a constraint to managing emergency maternal and neonatal complications including pre-eclampsia [27].…”
Section: Discussionsupporting
confidence: 85%